Splošna orientiranost študentov zdravstvene nege in zdravstvene vzgoje - Dornik, Ema (Obzornik zdravstvene nege, 1999)
The article presents part of a research work carried out in the frames of the health education studies. The author tried to find out whether any differencesexist between thestudents of health education and the students of nursing care as regards the concept of present social and living situation andtheir personal inclinations. The data gathered by a questionnaire applied to a sample of 118 students of nursing care and health education reveal some statistically significant differences in general orientation. With the development of education and activities of nursing care, nurses will be able to attain academic titles in Slovenia too.
Keywords: dejavnosti; education; Education, nursing, baccalaureate; Education, nursing, diploma programs; izobraževanje; Life style; Social values; student; Students, nursing; študenti; vrednote; zdravstvena nega; zdravstvena vzgoja